Nontargeted identification and predicted toxicity of new byproducts generated from UV treatment of water containing micropollutant 2-mercaptobenzothiazole. (1st January 2021) - Jiang, Ping; Qiu, Junlang; Gao, Yanpeng; Stefan, Mihaela I.; Li, Xing-Fang
Highlights: Developed a nontargeted strategy coupled with toxicity prediction of unknown TPs. Identified the structures of 9 new TPs in a total of 22 organic products. First time distinguished three isomeric products of 2-hydroxybenzothiazole. The 22 organic products accounted for 70% of 2-MBT photolysis. Majority of the organic products increase adverse effects on human thyroid function. Abstract: Comprehensive identification of byproducts including intermediate transformation products (TPs) of micropollutants in source water is challenging and paramount for assessment of drinking water quality and treatment technologies. Here, we have developed a nontargeted analysis strategy coupled with computational toxicity assessment to identify indistinguishable TPs including isomers with large differences in toxicity. The new strategy was applied to study the UV treatment of water containing micropollutant 2-mercaptobenzothiazole (2-MBT), and it enabled successful identification of a total of 22 organic TPs. Particularly, the structures of nine new TPs were identified for the first time; in addition, three isomers (P2, P3, and P4) were distinguished from the toxic contaminant 2-hydroxybenzothiazole (2-OH-BT). Computational assessments indicate that estrogenic activity of the three isomers (P2-P4) is higher than that of 2-OH-BT. Mass balance study shows that the 22 organic products accounted for 70% of the 2-MBT degraded, while 30% may degrade to inorganic products. Most TPs are resistant to UV photolysis. Computational toxicity assessment predicted the TPs to increase inhibition of human thyroperoxidase activity although they have lower aquatic toxicity compared to original 2-MBT. This study emphasizes the importance of monitoring the 2-MBT photodegradation products and the overall toxicity of finished water whose production included a UV light-based treatment process. Graphical abstract: Image, graphical abstract